Analyzing needs for designing a specific English language course for medical students in Bangladesh (Stamford Journal of English, 2013)
ESP (English for Specific Purposes) ensures designing courses to meet learners needs. Two vital devices of determining the needs are target needs and learning needs. The term target needs refers to what learners need to do in the target situation. It consists of three components- necessities, lacks, and wants. Learning needs are what learners need to do in order to learn. In designing an English course for the medical students, the research has focused on target needs and learning needs along with necessities, lacks, and wants. The medical students are really motivated by their subject specific texts. Most of the students suffer from the lack of adequate vocabulary. Their knowledge in the major areas of English grammar such as tense system, concept of voice, the syntax etc. is not sufficient. Their lack of the knowledge of the language is one of the prime reasons for their not being able to speak and write correctly and smoothly. A specific English language course can solve the problems by bridging their area related knowledge with their English language proficiency. Stamford Journal of English; Volume 6; Page 249-260 DOI: http://dx.doi.org/10.3329/sje.v6i0.13917